The impact of formal and non-formal education in the community of Callatiac, valley of Vilcanota, Cuzco. Mahía Maurial Mac Kee. Thesis presented to obtain the degree of Bachelor of Social Sciences specialized in Anthropology. September 1993 - Maurial Mackee, Mahía (1995)
The review does not present a summary.